The Fooling of Homeostasis Hypothesis Explains All What the Human Papillomavirus Infection does to the Cervix in Woman - Sinha, Pushpam Kumar (New Horizons in Medicine and Medical Research Vol. 2, 2022)
Low-grade Squamous Intraepithelial Lesion, High-grade Squamous Intraepithelial Lesion, and Cervical Cancer are the three most common cervix disease states after Human Papillomavirus infection. The objective of this study is to find a possible cure for Cervical Cancer by pin-pointing the genesis of all the three disease states of the cervix mentioned above. The genesis of all the three have been explained in this chapter using the Fooling of Homeostasis Hypothesis. According to this hypothesis, for cancers with stem cell origins, the would-be cancer cells just before turning cancerous undergo aggressive proliferation and aggressive apoptosis (at same rate) thereby leading to fooling of the homeostasis maintained by the surrounding healthy cells and immune cells. This hypothesis predicts that the possible cure for Cervical Cancer could be the use of chemicals ethanol-alcohol dehydrogenase and sodium metabisulphite.